Phytochemical composition, antioxidant and antiproliferative activities and effects on nuclear DNA of ethanolic extract from an Italian mycelial isolate of Ganoderma lucidum. (1st March 2019) - Saltarelli, Roberta; Palma, Francesco; Gioacchini, Anna Maria; Calcabrini, Cinzia; Mancini, Umberto; De Bellis, Roberta; Stocchi, Vilberto; Potenza, Lucia
Abstract: Ethnopharmacological relevance: Ganoderma lucidum (Curtis) P. Karst. (also known as Linghzhi and Reishi) is the most appreciated and revered medicinal mushroom across many Asian countries, but its properties have also attracted interest in Western countries. Indeed, in the West, it is now commercially available as a dietary supplement in preparations mainly made from spores, fruiting bodies and mycelia. It is employed in both nutraceutical and pharmacological formulations either for its immuno-modulating anti-inflammatory properties or as an effective adjuvant therapy in the treatment of several chronic diseases as well as in cancer treatment. Aim of the study: The aim of this investigation was to show the phytochemical composition and antioxidant and antiproliferative activities of an ethanolic extract from an Italian mycelial isolate of Ganoderma lucidum and to assess its effects on nuclear DNA. Materials and methods: LC/ESI-MS and tandem mass spectrometry MSMS were used to obtain structural identification of ethanolic G. lucidum extract constituents. Antioxidant activities were determined by the DPPH method, chelating effect on Fe 2+ and lipoxygenase inhibition while cytotoxic activities using the MTT assay. Effects on nuclear DNA were evaluated using the DNA nicking assay in a cell-free system and the fast halo assay performed on oxidatively injured human U937 cells; apoptosis induction was investigated using the non-denaturing fast halo assay and DNA laddering detection. Results: This extract was rich in several bioactive compounds, mainly phenolic and triterpenic acids. It showed antioxidant activity and protective effects in oxidatively injured DNA in cell-free analyses and antiproliferative, genotoxic, and proapoptotic effects in the cell model. Conclusions: Italian G. lucidum mycelium isolate appears to be a source of various natural compounds that may have applications as chemopreventive agents or functional foods. Graphical abstract: